The African Union and its institutions - Akokpari, John. (Auckland Park Fanele, 2008)
Written by eminent scholars on Africa and practitioners who have worked in or with the African Union (AU), this report brings together the analysis and research of 17 largely Pan-African scholars, policymakers, practitioners, and civil society representatives. A particularly timely and welcome addition to the pioneering literature about this young and potentially powerful institution, this analysis presents a positive but realistic picture of the AU while diagnosing several key challenges, including Africa?s security and governance problems.
Includes bibliographical references and index.
Keywords: African Union